Chitosan/Anthocyanin-Based Indicator Film with Carnauba Wax Addition for Monitoring Chicken Freshness - Wirda Roichatuttamamah; F. Widhi Mahatmanti; Samuel Budi Wardhana Kusuma; Endah Fitriani Rahayu (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
Indicator films can be applied to food packaging to monitor the quality of food products. However, chitosan/anthocyanin films tend to have low hydrophobicity, which may compromise their performance as indicators and lead to dye migration. One approach to address this issue is by incorporating additional materials such as carnauba wax. This study investigates the effect of carnauba wax addition on the mechanical properties and water contact angle of chitosan/anthocyanin-based indicator films, as well as evaluates the performance of the resulting films in monitoring the freshness of chicken meat. Indicator films were prepared by adding carnauba wax at concentrations of 6, 9, 12, and 15% (w/w of chitosan). The results showed that the addition of carnauba wax improved the mechanical properties of the films, although the improvement was not statistically significant. The best mechanical performance was observed with the 15% wax formulation. Additionally, the water contact angle increased with higher concentrations of carnauba wax, with the highest value (71.630°) observed for the CS/ABT/CW15% film. The indicator films were applied to chicken packaging and evaluated based on color changes during storage as a measure of freshness. After 30 hours, the film color changed from dark brown to green. The color change pattern during storage was similar for films with and without carnauba wax, indicating that the addition of carnauba wax does not affect the film’s ability to monitor chicken freshness.